Material Requirement Planning (MRP) Pada Pekerjaan Proyek Peningkatan Jalan Klasari-Wonosobo Kabupaten Sorong - Howay, Frans; Hanafi Ashad; Watono (Universitas Nusa Putra, 2025)
Material mobilization in Eastern Indonesia is different from other locations, difficult road access will cause large shipping prices, so it can affect the increase in the price of a material. The success of a construction work cannot be separated from the optimization of the implementation of three main components, namely cost, time and quality. Each component plays an important role and is interdependent with each other. One of the methods that may be used in material procurement planning is Material Requirement Planning or called MRP. From the problem of scheduling the arrival of materials in the Klasari – Wonosobo Road Improvement project, Sorong Regency, MRP (Material Requirement Planning) can be analyzed, starting with making project scheduling and then continuing with planning the ordering of materials needed during the project with the lot sizing method to produce more efficient material supply time so that it can be used and applied by contractors to plan more material purchases effective and efficient. The results of the research were the material needs of concrete road structures and talud structures in the Klasari-Wonosobo road improvement project in Sorong Regency using the requirement planning method, 925,161 kg of cement material was obtained; rough ggregate ; 2,288,752.50 kg ; Fine agregate 1,545,822 kg ; U24 plain iron 20,259.44 kg; U32 threaded iron 3,181.73 kg and water 490,074 liters. The material that is broken down is cement; rough agregate ; smooth agregate; U24 plain iron and U32 iron. In this MRP method, the material with the largest amount is the most suitable in terms of procurement, storage and use, namely coarse ggregate; 2,288,752.50 kg compared to other materials.